Composite magnetic powder and preparation method thereof

By modifying the composite magnetic powder of magnetic microparticles and nanoparticles, the problems of existing magnetic powder sealing materials agglomeration and poor sealing properties under high pressure conditions are solved, and good sealing performance and pressure resistance under high pressure are achieved.

CN119560251AActive Publication Date: 2025-03-04TSINGHUA UNIVERSITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510125685.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-27
Publication Date
2025-03-04
Estimated Expiration
2045-01-27

AI Technical Summary

Technical Problem

Existing magnetic powder sealing materials are prone to agglomeration under high pressure conditions, affecting their pressure resistance, while micron-scale magnetic powder has poor sealing properties and is prone to leakage.

Method used

The composite magnetic powder of modified magnetic microparticles and modified magnetic nanoparticles is modified by surfactant and combined with crosslinking agent to form a stable composite magnetic powder. It has high saturation magnetization and can withstand higher pressures, and has low porosity to reduce leakage of sealing media.

Benefits of technology

It achieves good sealing performance and pressure resistance under high pressure conditions, avoids agglomeration and leakage problems, and improves the overall performance of magnetic powder sealing materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of materials, and particularly relates to composite magnetic powder and a preparation method and application thereof. The composite magnetic powder comprises modified magnetic micro-particles and modified magnetic nano-particles, the modified magnetic micro-particles are magnetic micro-particles modified by a first surfactant, and the magnetic nano-particles are magnetic nano-particles modified by a second surfactant; the first surfactant comprises a double-hydrophilic-end surfactant, and the second surfactant comprises one or more of long-chain fatty acid, a silane coupling agent and a polymer. The composite magnetic powder has the beneficial effects that the composite magnetic powder has high saturation magnetization of the magnetic micron particles and can resist higher pressure; and meanwhile, the magnetic nanoparticles have low porosity, so that the leakage of a sealing medium can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of materials, and in particular relates to composite magnetic powder and a preparation method and application thereof. Background Art

[0002] Magnetic powder seal is a key technology widely used in mechanical seals, hydraulic seals and other fields. It has many advantages such as tight sealing, high temperature and high pressure resistance, low maintenance, high reliability, etc. The existing magnetic powder sealing materials mainly use nano-grade Fe3O4 magnetic powder. Although it has good sealing performance, pure nano-grade magnetic powder is prone to agglomeration under high pressure conditions, affecting its pressure resistance. Although micron-grade magnetic powder has good pressure resistance, its sealing is relatively poor and it is easy to leak.

[0003] The prior art discloses a method for preparing radiation-resistant magnetic particles, which can achieve effective sealing in the magnetic powder sealing process. However, since the magnetic particles prepared are all nano-scale, they are prone to agglomeration during the sealing process, affecting their pressure resistance. The prior art also discloses a method for preparing and synthesizing micron-sized magnetic particles. It has been proven that although micron-sized magnetic particles have good pressure resistance, their sealing performance is relatively poor and they are prone to leakage. In order to solve the above problems, it is of great practical significance to study a composite material containing both micron-sized and nano-sized Fe3O4 magnetic powders to take into account both sealing and pressure resistance. Summary of the invention

[0004] The present application provides a composite magnetic powder and a preparation method thereof, aiming to solve the problem that the existing magnetic powder cannot have good sealing properties and pressure resistance at the same time.

[0005] The first aspect of the present application provides a composite magnetic powder, comprising modified magnetic micron particles and modified magnetic nanoparticles, wherein the modified magnetic micron particles are magnetic micron particles modified by a first surfactant, and the magnetic nanoparticles are magnetic nanoparticles modified by a second surfactant; The first surfactant includes a double-hydrophilic-end surfactant, and the second surfactant includes one or more of a long-chain fatty acid, a silane coupling agent, and a polymer.

[0006] The composite magnetic powder described in the present application has both the high saturation magnetization strength of magnetic micron particles and can withstand higher pressures; and also contains the low porosity of magnetic nanoparticles, which can reduce the leakage of sealing media.

[0007] According to some embodiments of the composite magnetic powder described in the present application, the magnetic micron particles and the magnetic nanoparticles are each independently selected from one or more of Fe3O4, γ-Fe2O3 and ferrite magnetic particles.

[0008] According to some embodiments of the composite magnetic powder of the present application, the particle size of the magnetic micron particles is 10-20 μm.

[0009] According to some embodiments of the composite magnetic powder of the present application, the particle size of the magnetic nanoparticles is 1-10 nm.

[0010] According to some embodiments of the composite magnetic powder of the present application, the mass ratio of the modified magnetic micron particles to the modified magnetic nanoparticles is 1:9-9:1.

[0011] According to some embodiments of the composite magnetic powder described in the present application, the first surfactant includes one or more of glutamic acid, lysine, cysteine, sebacic acid, adipic acid, carboxyl-PEG-amine, thiol-PEG-carboxyl and dimercaptopropionic acid.

[0012] According to some embodiments of the composite magnetic powder of the present application, the molar ratio of the magnetic micron particles to the first surfactant in the modified magnetic micron particles is 1:(0.1-2).

[0013] According to some embodiments of the composite magnetic powder of the present application, the molar ratio of the magnetic nanoparticles to the second surfactant in the modified magnetic nanoparticles is 1:(0.1-2).

[0014] According to some embodiments of the composite magnetic powder described in the present application, the chemical formula of the ferrite magnetic particles is MFe2O4, wherein M includes one or more of Mn, Co, Ni, Cu, Cd, Pb, Sn, Ca, Sr, Ba and Mg.

[0015] According to some embodiments of the composite magnetic powder of the present application, the long-chain fatty acid includes one or more of oleic acid, stearic acid and palmitic acid.

[0016] According to some embodiments of the composite magnetic powder described in the present application, the silane coupling agent includes one or more of tetraethoxysilane, methacryloxypropyltriethoxysilane and octadecyltrimethoxysilane.

[0017] According to some embodiments of the composite magnetic powder described in the present application, the polymer includes one or more of polyethylene glycol, polyvinyl pyrrolidone and perfluoropolyether carboxylic acid.

[0018] According to some embodiments of the composite magnetic powder of the present application, the mass ratio of the modified magnetic micron particles to the modified magnetic nanoparticles is 3:7.

[0019] According to some embodiments of the composite magnetic powder of the present application, the particle size of the composite magnetic powder is 1-10 μm.

[0020] The second aspect of the present application provides a method for preparing the composite magnetic powder according to the first aspect of the present application, comprising the following steps: (1) Preparation of modified magnetic micron particles; (2) Preparation of modified magnetic nanoparticles; (3) Mixing the modified magnetic micron particles, the modified magnetic nanoparticles and a cross-linking agent to obtain the composite magnetic powder.

[0021] According to some embodiments of the method for preparing the composite magnetic powder described in the present application, in step (1), the method for preparing the modified magnetic micron particles includes the following steps: first mixing the magnetic micron particles, a first surfactant and a first solvent to obtain the modified magnetic micron particles.

[0022] According to some embodiments of the method for preparing the composite magnetic powder described in the present application, the method for preparing the modified magnetic micron particles further comprises subjecting the first mixed product to magnetic precipitation and washing treatment in sequence.

[0023] According to some embodiments of the method for preparing the composite magnetic powder described in the present application, the content of the first surfactant in each liter of the first solvent is 0.01-1 mol.

[0024] According to some embodiments of the method for preparing the composite magnetic powder described in the present application, the first solvent includes ethanol and / or deionized water.

[0025] According to some embodiments of the method for preparing the composite magnetic powder of the present application, the temperature of the first mixing is 20-80° C., the time of the first mixing is 1-180 min, and the rotation speed of the first mixing is 100-400 r / min.

[0026] According to some embodiments of the method for preparing the composite magnetic powder described in the present application, the washing includes washing with ethanol and deionized water in sequence.

[0027] According to some embodiments of the method for preparing the composite magnetic powder described in the present application, in step (2), the method for preparing the modified magnetic nanoparticles includes the following steps: performing a second mixing of the magnetic nanoparticles, a second surfactant, and a second solvent to obtain the modified magnetic nanoparticles.

[0028] According to some embodiments of the method for preparing the composite magnetic powder described in the present application, the method for preparing the modified magnetic nanoparticles further comprises subjecting the second mixed product to magnetic precipitation and washing treatment in sequence.

[0029] According to some embodiments of the method for preparing the composite magnetic powder described in the present application, the content of the second surfactant in each liter of the second solvent is 0.01-1 mol.

[0030] According to some embodiments of the method for preparing the composite magnetic powder of the present application, the second solvent includes ethanol and / or deionized water.

[0031] According to some embodiments of the method for preparing the composite magnetic powder of the present application, the temperature of the second mixing is 20-100° C., the time of the second mixing is 1-180 min, and the rotation speed of the second mixing is 100-400 r / min.

[0032] According to some embodiments of the method for preparing the composite magnetic powder described in the present application, the washing includes washing with ethanol and deionized water in sequence.

[0033] According to some embodiments of the method for preparing the composite magnetic powder described in the present application, in step (3), the mixing is performed in a third solvent, and the third solvent includes deionized water.

[0034] According to some embodiments of the method for preparing the composite magnetic powder described in the present application, the cross-linking agent includes one or more of glutaraldehyde, epichlorohydrin, hexamethylene diisocyanate and γ-aminopropyltriethoxysilane.

[0035] According to some embodiments of the method for preparing the composite magnetic powder of the present application, the mass ratio of the added amount of the cross-linking agent to the total amount of the modified magnetic micron particles and the modified magnetic nanoparticles is 1:(0.3-1).

[0036] According to some embodiments of the method for preparing the composite magnetic powder of the present application, in step (3), the mixing temperature is 20-100° C., the mixing time is 30-240 min, and the mixing speed is 100-200 r / min. DETAILED DESCRIPTION

[0037] The embodiments of the present invention are described in detail below, and are shown in the examples of the embodiments. The embodiments described below are exemplary and intended to be used to explain the present invention, but cannot be understood as limiting the present invention.

[0038] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0039] An embodiment of the present application provides a composite magnetic powder, including modified magnetic microparticles and modified magnetic nanoparticles, wherein the modified magnetic microparticles are magnetic microparticles modified by a first surfactant, and the magnetic nanoparticles are magnetic nanoparticles modified by a second surfactant; the first surfactant includes a double-hydrophilic end surfactant, and the second surfactant includes one or more of a long-chain fatty acid, a silane coupling agent and a polymer.

[0040] The composite magnetic powder described in the present application has both the high saturation magnetization strength of magnetic micron particles and can withstand higher pressures; and also contains the low porosity of magnetic nanoparticles, which can reduce the leakage of sealing media.

[0041] In some embodiments of the present application, the magnetic microparticles and the magnetic nanoparticles are independently selected from one or more of Fe3O4, γ-Fe2O3 and ferrite magnetic particles. The above particles have strong chemical stability, high and low temperature resistance, and high saturation magnetization.

[0042] In some embodiments of the present application, the chemical formula of the ferrite magnetic particles is MFe2O4, wherein M includes one or more of Mn, Co, Ni, Cu, Cd, Pb, Sn, Ca, Sr, Ba and Mg.

[0043] In some embodiments of the present application, the particle size of the magnetic micronized particles is 10-20 μm; In some embodiments of the present application, the particle size of the magnetic nanoparticles is 1-10 nm.

[0044] In some embodiments of the present application, the mass ratio of the modified magnetic micron particles to the modified magnetic nanoparticles is 1:9-9:1; for example, 1:9, 1:6, 1:5, 1:3, 1:1, 2:1, 3:1, 6:1, 9:1, etc. The high saturation magnetization of the magnetic micron particles can withstand higher pressures; the low porosity of the magnetic nanoparticles reduces the leakage of the sealing medium; the pressure resistance and leakage resistance properties can be adjusted by adjusting the mass ratio of the magnetic nanoparticles to the magnetic micron particles.

[0045] In some embodiments of the present application, the mass ratio of the modified magnetic microparticles to the modified magnetic nanoparticles is 3:7.

[0046] In some embodiments of the present application, the first surfactant includes one or more of glutamic acid, lysine, cysteine, sebacic acid, adipic acid, carboxyl-PEG-amine, thiol-PEG-carboxyl and dimercaptopropionic acid. The surfactant selected in the present application is a double-hydrophilic end surfactant, the end chain of which is a hydrophilic group such as amino, carboxyl, thiol, etc., which can be combined with Fe3O4 through hydrogen bonds or chemical bonds.

[0047] In some embodiments of the present application, the molar ratio of the magnetic micron particles to the first surfactant in the modified magnetic micron particles is 1:(0.1-2), such as 1:0.1, 1:0.5, 1:1, 1:1.2, 1:1.6, 1:2, etc. If the ratio of the surfactant is too low, the magnetic micron particles will not be completely coated by the surfactant and will be easily oxidized; if the ratio of the surfactant is too high, it will lead to over-coating, resulting in a decrease in saturation magnetization and agglomeration.

[0048] In some embodiments of the present application, the second surfactant includes one or more of long-chain fatty acids, silane coupling agents and polymers. The second surfactant selected in the present application can effectively prevent the magnetic nanoparticles from agglomerating. One end is a hydrophilic end that can combine with the magnetic particles, and the other end is a hydrophobic end that prevents the particles from being oxidized, thereby improving stability.

[0049] In some embodiments of the present application, the long-chain fatty acid includes one or more of oleic acid, stearic acid and palmitic acid.

[0050] In some embodiments of the present application, the silane coupling agent includes one or more of tetraethoxysilane (TEOS), methacryloxypropyltriethoxysilane (KH570) and octadecyltrimethoxysilane (OTMOS).

[0051] In some embodiments of the present application, the polymer includes one or more of polyethylene glycol, polyvinyl pyrrolidone and perfluoropolyether carboxylic acid.

[0052] In some embodiments of the present application, the molar ratio of the magnetic nanoparticles to the second surfactant in the modified magnetic nanoparticles is 1:(0.1-2), such as 1:0.1, 1:0.5, 1:1, 1:1.2, 1:1.6, 1:2, etc. If the ratio of the second surfactant is too low, the magnetic nanoparticles will not be completely coated by the second surfactant and will be easily oxidized; if the ratio of the second surfactant is too high, it will lead to over-coating, reduce the saturation magnetization intensity and cause agglomeration.

[0053] In some embodiments of the present application, the particle size of the composite magnetic powder is 1-10 μm.

[0054] The present application also provides a method for preparing the composite magnetic powder according to the first aspect of the present application, comprising the following steps: (1) Preparation of modified magnetic micron particles; (2) Preparation of modified magnetic nanoparticles; (3) Mixing the modified magnetic micron particles, the modified magnetic nanoparticles and a crosslinking agent to obtain the composite magnetic powder. Introducing a crosslinking agent during the preparation process of the composite magnetic powder of the present application can better improve the stability and high and low temperature resistance of the magnetic micron particles and nanoparticles. At the same time, the crosslinking agent can combine with the surfactant to form a three-dimensional network structure, thereby enhancing the pressure resistance and wear resistance in the magnetic powder seal.

[0055] In some embodiments of the present application, in step (1), the method for preparing the modified magnetic micron particles comprises the following steps: first mixing the magnetic micron particles, a first surfactant and a first solvent to obtain the modified magnetic micron particles.

[0056] In some embodiments of the present application, the content of the first surfactant per liter of the first solvent is 0.01-1 mol, for example, 0.01 mol, 0.05 mol, 0.08 mol, 0.5 mol, 0.6 mol, 0.8 mol, 1 mol, etc.

[0057] In some embodiments of the present application, the first solvent includes ethanol and / or deionized water.

[0058] In some embodiments of the present application, the temperature of the first mixing is 20-80°C, such as 20°C, 30°C, 50°C, 80°C, etc., the time of the first mixing is 1-180min, such as 1min, 10min, 50min, 78min, 86min, 95min, 110min, 125min, 130min, 160min, 180min, etc., and the speed of the first mixing is 100-400r / min, such as 100r / min, 120r / min, 150r / min, 180r / min, 200r / min, 260r / min, 290r / min, 320r / min, 400r / min, etc. If the mixing temperature is too low, the reaction rate will be too slow, the formed magnetic particles will be unstable, and the coating magnetization intensity will be unsatisfactory; if the temperature is too high, the generated Fe3O4 will be directly oxidized to Fe2O3.

[0059] In some embodiments of the present application, the method for preparing the modified magnetic micron particles further comprises filtering and washing the first mixed product in sequence; preferably, the washing comprises washing with ethanol and deionized water in sequence; washing is repeated until the pH of the eluate is 7, and then vacuum drying is performed.

[0060] In some embodiments of the present application, the method for preparing the magnetic micronized particles comprises the following steps: 2+ and Fe 3+The molar ratio of FeCl3•6H2O and FeCl2•4H2O is 0.5-0.75:1. Dissolve FeCl3•6H2O and FeCl2•4H2O in deionized water, add sodium citrate or PVP as a crystal control agent, and adjust the molar ratio of Fe 3+ :Crystal form control agent = 1:0.2-1 ratio, and NaOH is added to adjust the pH of the solution to 10-12; the reaction temperature is controlled at 25-100°C, the stirring speed is 200r / min-500r / min, and the reaction time under this condition is 10min-120min to form Fe(OH)3 precipitation. The Fe(OH)3 precipitation obtained by the reaction is moved to a high-pressure reactor, and subjected to high-pressure hydrothermal reaction at 150-200°C for 5-8h, cooled naturally to room temperature, repeatedly washed with deionized water until the pH of the eluate is 7, and vacuum dried to obtain micron-sized magnetic micron particles.

[0061] In some embodiments of the present application, in step (2), the method for preparing the modified magnetic nanoparticles comprises the following steps: performing a second mixing of the magnetic nanoparticles, a second surfactant and a second solvent to obtain the modified magnetic nanoparticles.

[0062] In some embodiments of the present application, the content of the second surfactant in each liter of the second solvent is 0.01-1 mol; for example, 0.01 mol, 0.05 mol, 0.1 mol, 0.2 mol, 0.3 mol, 0.5 mol, 0.8 mol, 1 mol, etc.

[0063] In some embodiments of the present application, the second solvent includes ethanol and / or deionized water.

[0064] In some embodiments of the present application, the temperature of the second mixing is 20-100°C, such as 20°C, 30°C, 50°C, 80°C, 100°C, etc., the time of the second mixing is 1-180min, such as 1min, 10min, 50min, 78min, 86min, 95min, 110min, 125min, 130min, 160min, 180min, etc., and the speed of the second mixing is 100-400r / min; such as 100r / min, 120r / min, 150r / min, 180r / min, 200r / min, 260r / min, 290r / min, 320r / min, 400r / min, etc. If the mixing temperature is too low, it will lead to uneven coating and a thin coating layer; if the mixing temperature is too high, it may cause thermal decomposition of the coating material and oxidation of the magnetic particles.

[0065] In some embodiments of the present application, the method for preparing the modified magnetic nanoparticles further comprises filtering and washing the second mixed product in sequence; preferably, the washing comprises washing with ethanol and deionized water in sequence, repeatedly washing until the pH of the eluate is 7, and then vacuum drying.

[0066] In some embodiments of the present application, magnetic nanoparticles are prepared by coprecipitation method, and the specific steps include: 2+ , Fe 3+ OH - The molar ratio is (0.5-0.75):1:(4-4.5). FeCl3•6H2O and FeCl2•4H2O are dissolved in deionized water and stirred evenly to obtain a mixed iron salt solution. Ammonia water is added to the mixed iron salt solution. The reaction temperature is controlled to be 25-100°C and the stirring speed is 200-500r / min. Under this condition, the reaction is carried out for 1-60min. The obtained product is repeatedly washed with deionized water until the pH of the eluate is 7, and vacuum dried to obtain magnetic nanoparticles.

[0067] In some embodiments of the present application, the cross-linking agent includes glutaraldehyde, epichlorohydrin, hexamethylene diisocyanate, and γ-aminopropyltriethoxysilane (APTES). The cross-linking agent glutaraldehyde described in the present application contains aldehyde groups at both ends, which can react with amino groups to form imines, and can react with carboxylic acids to form esters for cross-linking; at the same time, epichlorohydrin contains epoxy groups and hexamethylene diisocyanate contains isocyanate groups -NCO, which can react with amino groups and carboxyl groups for cross-linking.

[0068] In some embodiments of the present application, the mass ratio of the added amount of the cross-linking agent to the total amount of the modified magnetic microparticles and the modified magnetic nanoparticles is 1:(0.3-1), for example, 1:0.3, 1:0.5, 1:0.7, 1:0.9, 1:1, etc.

[0069] In some embodiments of the present application, in step (3), the mixing is performed in a third solvent, and the third solvent includes deionized water.

[0070] In some embodiments of the present application, in step (3), the mixing temperature is 20-100°C, such as 20°C, 25°C, 30°C, 35°C, 40°C, 50°C, 60°C, 80°C, 100°C, etc., the mixing time is 30-240min, such as 30min, 80min, 100min, 120min, 160min, 180min, 240min, etc., and the mixing speed is 100-200r / min, such as 100r / min, 110r / min, 120r / min, 150r / min, 160r / min, 180r / min, 200r / min, etc. If the mixing temperature is too low, the cross-linking is slow, and if the mixing temperature is too high, the surfactant may fail.

[0071] The technical solution of this application is further explained below in conjunction with specific implementation cases.

[0072] Example 1 A method for preparing composite magnetic powder comprises the following steps: Weigh 11g of FeCl3•6H2O and 9.7g of FeCl2•4H2O and dissolve them in 400ml of deionized water, add 5g of sodium citrate, slowly add 2mol / l NaOH solution until the pH of the solution is 10, stir the reaction at 80℃ at a speed of 400r / min for 1h, and it can be observed that the solution turns into a black suspension, proving that iron ions have begun to precipitate. Transfer the suspension generated by the above reaction to a high-pressure reactor and seal it. Carry out hydrothermal reaction at 180℃ and 1MPa for 12 hours. After cooling naturally to room temperature, take out the reaction product, place the prepared solution on a permanent magnet to separate the solvent and magnetic particles, wash it repeatedly with deionized water five times until the pH of the eluate is 7, and vacuum dry it to obtain micron-sized magnetic micron particles.

[0073] 11g of Fe3O4 magnetic micron particles with a particle size of 10μm were dispersed again in 400ml of deionized water, and 1g of glutamic acid surfactant was added and stirred evenly to form a suspension. The suspension was heated to 60°C in a water bath and kept warm for 60min at a stirring speed of 400r / min. After the reaction was completed, the reaction solution was cooled naturally and cooled to room temperature. The black solid was magnetically separated and repeatedly washed with ethanol and deionized water until the pH of the eluate was 7. The modified Fe3O4 micron-sized magnetic micron particles were obtained by vacuum drying.

[0074] Weigh 25.6g of FeCl3•6H2O and 22.6g of FeCl2•4H2O, dissolve in 400mL of deionized water, slowly add 100ml of 2mol / l NaOH solution, stir at 400r / min and 40℃ for 1h, it can be observed that the mixed solution quickly changes from yellow to black. After the reaction is completed, magnetic particles are magnetically separated and washed repeatedly with deionized water five times until the pH of the eluate is 7, and then vacuum dried to obtain Fe3O4 nanoscale magnetic nanoparticles.

[0075] 27g of Fe3O4 magnetic nanoparticles with a particle size of 10nm were dispersed again in 400ml of deionized water, and 1g of oleic acid surfactant was added and stirred evenly to form a suspension. The suspension was heated to 80°C in a water bath and kept warm for 60min at a stirring speed of 400r / min. After the reaction was completed, the reaction solution was cooled naturally. After it was cooled to room temperature, the black solid was magnetically separated and repeatedly washed with ethanol and deionized water until the pH of the eluate was 7 to obtain a solution of modified Fe3O4 magnetic nanoparticles.

[0076] 12g of modified Fe3O4 magnetic micron particles and 28g of modified Fe3O4 magnetic nanoparticles were dissolved in deionized water, and 2ml of 25% glutaraldehyde solution was added as a cross-linking agent. The mixture was stirred at 200r / min at 40°C for 2h. After the reaction was completed, the magnetic particles were magnetically separated and repeatedly washed with deionized water until the pH of the eluate was 7. The composite magnetic powder with stable nano-nano particle size of 10μm was obtained by vacuum drying.

[0077] Example 2 A method for preparing composite magnetic powder comprises the following steps: Weigh 11g of FeCl3•6H2O and dissolve it in 400ml of deionized water, add 5g of sodium citrate, slowly add 2mol / l NaOH solution until the pH of the solution is 10, stir the reaction at 80℃ at a speed of 400r / min for 1h, and it can be observed that the solution turns into a black suspension, proving that the iron ions have begun to precipitate. Transfer the suspension generated by the above reaction to a high-pressure reactor and seal it. Carry out hydrothermal reaction at 180℃ and 1MPa for 12 hours. After cooling naturally to room temperature, take out the reaction product, place the prepared solution on a permanent magnet to separate the solvent and magnetic particles, wash it repeatedly with deionized water five times until the pH of the eluate is 7, and vacuum dry it to obtain micron-sized magnetic micron particles.

[0078] 3 g of γ-Fe2O3 magnetic micron particles with a particle size of 10 μm were dispersed again in 400 ml of deionized water, and 1 g of glutamic acid surfactant was added and stirred evenly to form a suspension. The suspension was heated to 60°C in a water bath and kept warm for 60 minutes at a stirring speed of 400 r / min. After the reaction was completed, the reaction solution was cooled naturally and cooled to room temperature. The black solid was magnetically separated and repeatedly washed with ethanol and deionized water until the pH of the eluate was 7. The modified γ-Fe2O3 micron-sized magnetic micron particles were obtained by vacuum drying.

[0079] Weigh 25.6 g of FeCl3•6H2O and dissolve it in 400 mL of deionized water. Slowly add 2 mol / l NaOH solution until the pH of the solution reaches 10. Stir at 400 r / min and 40°C for 1 h. After the reaction is completed, magnetic particles are separated by magnetism and washed repeatedly with deionized water five times until the pH of the eluate is 7. Vacuum dry to obtain γ-Fe2O3 nanoscale magnetic nanoparticles.

[0080] 7 g of γ-Fe2O3 magnetic nanoparticles with a particle size of 10 nm were dispersed again in 400 ml of deionized water, and 1 g of oleic acid surfactant was added and stirred evenly to form a suspension. The suspension was heated to 80°C in a water bath and kept warm for 60 minutes at a stirring speed of 400 r / min. After the reaction was completed, the reaction solution was naturally cooled. After it was cooled to room temperature, the black solid was magnetically separated and repeatedly washed with ethanol and deionized water until the pH of the eluate was 7 to obtain a solution of modified γ-Fe2O3 magnetic nanoparticles.

[0081] 4g of modified γ-Fe2O3 magnetic micron particles and 8g of modified γ-Fe2O3 magnetic nanoparticles were dissolved in deionized water, and 2ml of 25% glutaraldehyde solution was added as a cross-linking agent. The mixture was stirred at 200r / min at 40°C for 2h. After the reaction was completed, the magnetic particles were magnetically separated and repeatedly washed with deionized water until the pH of the eluate was 7. The particles were then vacuum dried to obtain stable nano- and micro-nano-composite magnetic powders with a particle size of 10μm.

[0082] Example 3 A method for preparing composite magnetic powder comprises the following steps: Weigh 8g of CoCl2•6H2O and 11g of FeCl3·6H2O, dissolve in 400ml of deionized water, add 5g of sodium citrate, slowly add 2mol / l NaOH solution until the pH of the solution is 10, stir the reaction at 80℃ at a speed of 400r / min for 1h, and it can be observed that the solution turns into a black suspension, proving that the iron ions have begun to precipitate. Transfer the suspension generated by the above reaction to a high-pressure reactor and seal it. Carry out hydrothermal reaction at 180℃ and 1MPa for 12 hours. After cooling naturally to room temperature, take out the reaction product, place the prepared solution on a permanent magnet to separate the solvent and magnetic particles, wash it repeatedly with deionized water five times until the pH of the eluate is 7, and vacuum dry it to obtain micron-sized magnetic micron particles.

[0083] 4.8 g of CoFe2O4 magnetic micron particles with a particle size of 10 μm were dispersed again in 400 ml of deionized water, and 1 g of glutamic acid surfactant was added and stirred evenly to form a suspension. The suspension was heated to 60°C in a water bath and kept warm for 60 minutes at a stirring speed of 400 r / min. After the reaction was completed, the reaction solution was cooled naturally and cooled to room temperature. The black solid was magnetically separated and repeatedly washed with ethanol and deionized water until the pH of the eluate was 7. The modified CoFe2O4 micron-sized magnetic micron particles were obtained by vacuum drying.

[0084] Weigh 18.7 g of CoCl2•6H2O and 25.6 g of FeCl3·6H2O and dissolve them in 400 mL of deionized water. Slowly add 2 mol / l NaOH solution until the pH of the solution reaches 10. Stir at 400 r / min and 40°C for 1 h. After the reaction is completed, magnetic particles are magnetically separated and washed repeatedly with deionized water five times until the pH of the eluate is 7. Vacuum dry to obtain CoFe2O4 nanoscale magnetic nanoparticles.

[0085] 11.2 g of CoFe2O4 magnetic nanoparticles with a particle size of 10 nm were dispersed again in 400 ml of deionized water, and 1 g of oleic acid surfactant was added and stirred evenly to form a suspension. The suspension was heated to 80°C in a water bath and kept warm for 60 minutes at a stirring speed of 400 r / min. After the reaction was completed, the reaction solution was naturally cooled. After it was cooled to room temperature, the black solid was magnetically separated and repeatedly washed with ethanol and deionized water until the pH of the eluate was 7 to obtain a solution of modified CoFe2O4 magnetic nanoparticles.

[0086] 5.8g of modified CoFe2O4 magnetic micron particles and 5.8g of modified CoFe2O4 magnetic nanoparticles were dissolved in deionized water, and 2ml of 25% glutaraldehyde solution was added as a cross-linking agent. The mixture was stirred at 200r / min at 40°C for 2h. After the reaction was completed, the magnetic particles were magnetically separated and repeatedly washed with deionized water until the pH of the eluate was 7. The composite magnetic powder with stable nano-nano particle size of 10μm was obtained by vacuum drying.

[0087] Example 4 The only difference between Example 4 and Example 1 is that lysine is used to modify the magnetic micron particles in the composite magnetic powder described in Example 4.

[0088] Example 5 The only difference between Example 5 and Example 1 is that adipic acid is used to modify the magnetic micron particles in the composite magnetic powder described in Example 5.

[0089] Example 6 The only difference between Example 6 and Example 1 is that dimercaptopropionic acid is used to modify the magnetic micron particles in the composite magnetic powder described in Example 6.

[0090] Example 7 The only difference between Example 7 and Example 1 is that the mass ratio of the modified Fe3O4 magnetic micron particles and the modified Fe3O4 magnetic nanoparticles in the composite magnetic powder of Example 7 is 2:8.

[0091] Example 8 The only difference between Example 8 and Example 1 is that the mass ratio of the modified Fe3O4 magnetic micron particles and the modified Fe3O4 magnetic nanoparticles in the composite magnetic powder of Example 8 is 1:9.

[0092] Example 9 The only difference between Example 9 and Example 1 is that the mass ratio of the modified Fe3O4 magnetic micron particles and the modified Fe3O4 magnetic nanoparticles in the composite magnetic powder of Example 9 is 1:1.

[0093] Example 10 The only difference between Example 10 and Example 1 is that the mass ratio of the modified Fe3O4 magnetic micron particles to the modified Fe3O4 magnetic nanoparticles in the composite magnetic powder of Example 10 is 7:3.

[0094] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in the composite magnetic powder of Comparative Example 1, the second surfactant is used to modify the magnetic micron particles, and the first surfactant is used to modify the magnetic nanoparticles.

[0095] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the magnetic nanoparticles in the composite magnetic powder of Comparative Example 2 are modified by using a first surfactant.

[0096] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the magnetic micron particles are modified by using a second surfactant in the composite magnetic powder described in Comparative Example 3.

[0097] Performance study of the composite magnetic powders described in Examples 1-11 and Comparative Examples 1-3 of the present application: Experimental method: The composite magnetic powder described in Examples 1-9 and Comparative Examples 1-3 of the present application is modeled and simulated by COMSOL Multiphysics to obtain the permeability of different magnetic particles, which is used to describe the difficulty of fluid passing through porous media under a certain driving force, reflecting its leakage resistance; the saturation magnetization intensity of each magnetic powder is analyzed by a vibrating sample magnetometer (VSM) to reflect its pressure resistance; the color of the magnetic powder is observed by naked eyes to determine the oxidation days to compare the stability of the magnetic particles.

[0098] The test results are shown in Table 1: Table 1

[0099] From Table 1 we can see that: Through the analysis of Examples 1-3, it can be found that when Fe3O4, γ-Fe2O3, and CoFe2O4 are used to prepare micro-nano composite magnetic powder, their particle permeability and stability show relatively similar performance, and the difference is not significant. In terms of the key indicator of saturation magnetization, the three have a magnitude relationship of Fe3O4>γ-Fe2O3>CoFe2O4. This result indirectly shows that the micro-nano composite magnetic powder prepared based on Fe3O4 has better pressure resistance and can withstand greater pressure while maintaining a better performance state.

[0100] Through the analysis of Example 1 and Example 4-6, it can be found that the influence of different first surfactants on the saturation magnetization is relatively small. In terms of permeability, it shows a law of increasing in the order of glutamic acid, lysine, adipic acid, and dimercaptopropionic acid. In terms of stability, according to the oxidation days, glutamic acid performs best, while lysine, adipic acid, and dimercaptopropionic acid weaken in turn. It is inferred that this may be caused by the fact that the aldehyde group in the cross-linking agent glutaraldehyde has a decreasing bonding stability to the amino group, carboxyl group, and sulfhydryl group.

[0101] By analyzing Example 1 and Examples 7-10, it can be seen that the saturation magnetization of the composite magnetic powder shows a trend of increasing with the increase of the mass ratio of magnetic micron particles to magnetic nanoparticles. However, when the mass ratio of the two reaches 3:7, even if the proportion of magnetic micron particles is further increased, the growth rate of the saturation magnetization of the composite magnetic powder is extremely limited, almost negligible, and close to no growth; on the other hand, the permeability change law of the composite magnetic powder is shown as increasing accordingly with the decrease of the mass ratio of magnetic micron particles and magnetic nanoparticles. However, when the mass ratio is 3:7, if the proportion of magnetic nanoparticles continues to increase, the decrease in the permeability of the composite magnetic powder is minimal, and it can be basically determined that there is no significant decrease. The above experimental results show that when the mass ratio of magnetic micron particles and magnetic nanoparticles is exactly 3:7, the composite magnetic powder exhibits the strongest pressure resistance, and its permeability is also minimized.

[0102] Through the analysis of Example 1 and Comparative Example 1, it can be seen that when the second surfactant is used to modify the magnetic micron particles and the first surfactant is used to modify the magnetic nanoparticles, the saturation magnetization intensity of the composite magnetic powder obtained is not significantly affected. However, the leakage rate of Comparative Example 1 is significantly higher than that of Example 1, and its stability is also much lower than that of Example 1, which is much lower than the stability level of Example 1.

[0103] Further comparison between Example 1 and Comparative Example 2 shows that when the first surfactant is used to modify the magnetic nanoparticles, the saturation magnetization of Comparative Example 2 is significantly lower than that of Example 1, while its leakage rate is higher than that of Example 1, and its stability is far inferior to that of Example 1. It is speculated through analysis that this may be due to the simultaneous introduction of the double-hydrophilic end surfactant, which causes the magnetic particles to be over-coated, thereby reducing the saturation magnetization and causing the problem of particle agglomeration, which ultimately has a negative impact on its performance.

[0104] Further analysis of Example 1 and Comparative Example 3 shows that after the magnetic micronized particles are modified by the second surfactant, the obtained saturation magnetization and leakage rate are similar to those of Example 1, but the stability is significantly lower than that of Example 1. After in-depth analysis, it is believed that this may be due to the incomplete coating process and the poor effect of the cross-linking agent, which reduces the stability of the particles and cannot reach the stability of Example 1.

[0105] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.

Claims

1. A composite magnetic powder, characterized in that: The modified magnetic micron particles and modified magnetic nanoparticles are included, wherein the modified magnetic micron particles are magnetic micron particles modified by a first surfactant, and the magnetic nanoparticles are magnetic nanoparticles modified by a second surfactant; The first surfactant includes a double-hydrophilic-end surfactant, and the second surfactant includes one or more of a long-chain fatty acid, a silane coupling agent, and a polymer.

2. The composite magnetic powder according to claim 1, characterized in that: The magnetic micron particles and the magnetic nanoparticles are independently selected from one or more of Fe3O4, γ-Fe2O3 and ferrite magnetic particles; And / or, the particle size of the magnetic micronized particles is 10-20 μm; And / or, the particle size of the magnetic nanoparticles is 1-10 nm; And / or, the mass ratio of the modified magnetic micron particles to the modified magnetic nanoparticles is 1:9-9:

1.

3. The composite magnetic powder according to claim 2, characterized in that: The first surfactant comprises one or more of glutamic acid, lysine, cysteine, sebacic acid, adipic acid, carboxyl-PEG-amine, thiol-PEG-carboxyl and dimercaptopropionic acid; and / or, the molar ratio of the magnetic microparticles to the first surfactant in the modified magnetic microparticles is 1:(0.1-2); And / or, the molar ratio of the magnetic nanoparticles to the second surfactant in the modified magnetic nanoparticles is 1:(0.1-2).

4. The composite magnetic powder according to claim 3, characterized in that: The chemical formula of the ferrite magnetic particles is MFe2O4, wherein M includes one or more of Mn, Co, Ni, Cu, Cd, Pb, Sn, Ca, Sr, Ba and Mg; and / or, the long-chain fatty acid comprises one or more of oleic acid, stearic acid and palmitic acid; And / or, the silane coupling agent includes one or more of tetraethoxysilane, methacryloxypropyltriethoxysilane and octadecyltrimethoxysilane; and / or, the polymer comprises one or more of polyethylene glycol, polyvinyl pyrrolidone and perfluoropolyether carboxylic acid; and / or, the mass ratio of the modified magnetic micron particles to the modified magnetic nanoparticles is 3:7; And / or, the particle size of the composite magnetic powder is 1-10 μm.

5. The method for preparing the composite magnetic powder according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Preparation of modified magnetic micron particles; (2) Preparation of modified magnetic nanoparticles; (3) Mixing the modified magnetic micron particles, the modified magnetic nanoparticles and a cross-linking agent to obtain the composite magnetic powder.

6. The method for preparing composite magnetic powder according to claim 5, characterized in that: In step (1), the method for preparing the modified magnetic micron particles comprises the following steps: first mixing the magnetic micron particles, a first surfactant and a first solvent to obtain the modified magnetic micron particles; And / or, the method for preparing the modified magnetic micron particles further comprises subjecting the first mixed product to magnetic precipitation and washing treatment in sequence.

7. The method for preparing composite magnetic powder according to claim 6, characterized in that: The content of the first surfactant in each liter of the first solvent is 0.01-1 mol; and / or, the first solvent comprises ethanol and / or deionized water; And / or, the temperature of the first mixing is 20-80° C., the time of the first mixing is 1-180 min, and the speed of the first mixing is 100-400 r / min; And / or, the washing comprises washing with ethanol and deionized water in sequence.

8. The method for preparing composite magnetic powder according to claim 5, characterized in that: In step (2), the method for preparing the modified magnetic nanoparticles comprises the following steps: performing a second mixing of the magnetic nanoparticles, a second surfactant and a second solvent to obtain the modified magnetic nanoparticles; And / or, the method for preparing the modified magnetic nanoparticles further comprises subjecting the second mixed product to magnetic precipitation and washing treatment in sequence.

9. The method for preparing composite magnetic powder according to claim 8, characterized in that: The content of the second surfactant in each liter of the second solvent is 0.01-1 mol; and / or, the second solvent comprises ethanol and / or deionized water; And / or, the temperature of the second mixing is 20-100° C., the time of the second mixing is 1-180 min, and the speed of the second mixing is 100-400 r / min; And / or, the washing comprises washing with ethanol and deionized water in sequence.

10. The method for preparing composite magnetic powder according to claim 5, characterized in that: In step (3), the mixing is performed in a third solvent, and the third solvent includes deionized water; and / or, the cross-linking agent comprises one or more of glutaraldehyde, epichlorohydrin, hexamethylene diisocyanate and γ-aminopropyltriethoxysilane; And / or, the mass ratio of the added amount of the cross-linking agent to the total amount of the modified magnetic microparticles and the modified magnetic nanoparticles is 1:(0.3-1); And / or, in step (3), the mixing temperature is 20-100° C., the mixing time is 30-240 min, and the mixing speed is 100-200 r / min.

Citation Information

Patent Citations

  • Preparation method of ferroferric oxide / gold nanocomposite particles

    CN110211758A

  • Nanometer magnetic particle, preparation method thereof and magnetic liquid

    CN114496442A

  • Preparation method of magnetic polyurethane microcapsule and capsule targeting distribution method in composite epoxy resin

    CN118217895A

  • Method for functionalization on magnetic nano particle surface

    CN1990528A

  • Nanostructured magnetorheological fluids and gels

    US20050109976A1